QUANTITY AND GEOCHEMICAL PROPERTIES OF MOLYBDENUM IN SALINE SOILS (American Journal of Pedagogical and Educational Research, 2025)
Today, the practice of farming in irrigated areas in the world, the study of the chemical and geochemical properties of saline soils from a pedogeochemical point of view, the study of chemical elements in agrolandscapes in the chain of plant-soil-mother rock and soil layers are among the urgent problems of our time.